Disease Control in Animals Using Molecular Technology by Inactivation of ASO, RNAi and ss-siRNA Genes - Ali, Muhamad (Indonesian Animal Sciences Society, 2014)
Globalization causes high mobility of human and livestock, hence increase the transmission of infectious diseases, including avian influenza, severe acute respiratory syndrome (SARS), and swine influenza. Therefore, prevention of those diseases is required. Vaccines are effective to prevent infectious diseases; however, their development takes a long time and they cannot provide immediate protection in pandemic cases. This paper describes several gene silencing technologies including antisense oligonucleotide (ASO), RNA interference (RNAi) and single strand-small interfering RNA (ss-siRNA) for controlling diseases. The primary mechanism of these technologies is inhibition of gene expression, typically by causing the destruction of specific RNA molecule of the pathogen. The use of gene silencing technologies is expected to give new alternative that is more effective in eradication of infectious diseases in animals before threaten human being. Key words: Gene inactivation, antisense oligonucleotide, RNA interference, single strand-small interfering RNA